The effects of different protease treatments on the techno-functional, structural, and bioactive properties of bovine casein. Issue 10 (1st November 2022) - Bekiroglu, Hatice; Bozkurt, Fatih; Karadag, Ayse; Ahhmed, Abdulatef M.; Sagdic, Osman
Abstract: In this study, bovine sodium caseinate (NaCas) was hydrolyzed with four proteases, alcalase, savinase, subtilisin A, and flavourzyme. In addition to the structural changes occurred through the enzymatic hydrolysis, the solubility, oil binding capacity, zeta potential, emulsification properties, and in vitro antioxidant capacity, anti-carcinogenic and antidiabetic properties of hydrolysates were determined. FTIR combined with hierarchical cluster analysis (HCA) made in Amide I region enable to classification of the samples based on the changes of the secondary structure depending on the enzyme type and degree of fragmentation. Technological properties of NaCas were enhanced through the enzymatic hydrolysis, and those were more prominent in serine-type enzymes, regardless of the enzyme type, all hydrolysates showed high antioxidant capacities. All hydrolysates, specifically those produced by savinase and alcalase, reduced the viability of the carcinogenic Caco-2 cells in a dose-dependent manner and showed a very low level of cytotoxicity against healthy HEK-293 cells. The hydrolysis treatment made a significant contribution to the antidiabetic activity of NaCas. Particularly alcalase and savinase hydrolysates suppressed the activity of α- amylase and α- glucosidase. Therefore, the generated milk protein hydrolysates could be used in functional food developments for specific dietary purposes.